2012
DOI: 10.1002/stem.1052
|View full text |Cite
|
Sign up to set email alerts
|

CD49f Enhances Multipotency and Maintains Stemness Through the Direct Regulation of OCT4 and SOX2

Abstract: CD49f (integrin subunit a6) regulates signaling pathways in a variety of cellular activities. However, the role of CD49f in regulating the differentiation and pluripotency of stem cells has not been fully investigated. Therefore, in this study, human mesenchymal stem cells (hMSCs) were induced to form spheres under nonadherent culture conditions, and we found that the CD49f-positive population was enriched in MSC spheres compared with MSCs in a monolayer. The expression of CD49f regulated the ability of hMSCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 52 publications
5
118
1
Order By: Relevance
“…In particular, many reports have shown that integrin signalling regulates stem cell differentiation (Smadja et al, 2014;Yu et al, 2012). These results indicate that control of integrin signalling is valuable for stem cell regulation.…”
Section: Discussionmentioning
confidence: 84%
“…In particular, many reports have shown that integrin signalling regulates stem cell differentiation (Smadja et al, 2014;Yu et al, 2012). These results indicate that control of integrin signalling is valuable for stem cell regulation.…”
Section: Discussionmentioning
confidence: 84%
“…37 CD49f has been used for enrichment of normal cells and CSCs, 38,39 which maintains the pluripotency and stemness through the direct regulation of OCT4 and SOX2. 40 In our study, transcriptional factors related to stem cells, including SOX2 and OCT3/4, and breast CSC signatures, including SOX4 and CD49f, were enhanced in MCF-7 cultured on fibrous scaffolds by 1.77 AE 0.25-fold, 2.22 AE 0.23-fold, 1.56 AE 0.25-fold, and 2.92 AE 0.33-fold, respectively, relative to cells on TCP (Fig. 5a).…”
Section: Cellular Morphology and Growth On Electrospun Pcl 3d Scaffoldsmentioning
confidence: 99%
“…They also suggested that BCSCs would be enriched in the CD44 + CD24 -cells if they were combined with the CD49f + phenotype (Ghebeh et al, 2013). CD49f was also determined as a marker of BCSCs in previous studies (Meyer et al, 2010;Yu et al, 2012 However, Medium D and Medium M also supported stromal cell proliferation. Regarding CD90 expression, more than 50% of the primary cells in Medium D and Medium M tested positive for this marker, whereas this population only accounted for about 25% of the primary cells grown in Medium DB.…”
Section: Discussionmentioning
confidence: 97%